Anionic effect on nanostructure and morphology of bio-schwertmannite dynamically produced within cellular reproduction. (27th October 2020) - Xiong, Huixin; Lu, Xiancai; Wang, Rucheng
Schwertmannite has been considered as the host mineral and potentially excellent adsorbent of contaminates from waters, and it has various morphologies of spheroid with pincushions, whiskers, hedge-hogs, and needles. In this work, using the (high-resolution transmission and field-emission scanning) electron microscopes, we studied nanostructure, morphological evolution, and difference in chemical composition for the produced schwertmannites in the cell-rich iron solutions. All analysis results showed within cellular 36-h reproduction period, the production of only schwertmannite was examined in iron solutions at the Cl − /SO4 2− molar ratios of 0–10 and pH 3.0 ± 0.1. There were differences in two typical morphologies of "pincushions" (Cl − /SO4 2− = 0 and 3) and "hedge-hogs" (Cl − /SO4 2− = 6 and 10) for the schwertmannite nanostructures. And all final schwertmannite particles had the chemical formulas of Fe8 O8 (OH)8−2 x (SO4 ) x (1.08 ≤ x ≤ 1.66), especially as Cl − /SO4 2− = 0, the visible "pincushions" only being the outermost sections of the whole needles existing in a tightly spherical assemblage of schwertmannite. Moreover, the absence of ferrihydrite and goethite was determined in the nanodimension of these needles, though the initial Fe and SO4 2− were 5600 and of 9600 µg/mL, respectively. It could be induced by the amounts and activities of aqueous Fe, SO4 2−, and Cl − associated with cellular activities and mineral precipitation. This study will be useful for understanding the actual occurrence of iron oxyhydroxide nanostructure and better developing its potential environmental application.